No Added Benefit from EC-IC Bypass Surgery When Added to Standard Medical Therapy in Preventing Recurrence of Ipsilateral Stroke - Vinall, Maria (MD Conference Express, 2011)
Results from the Carotid Occlusion Surgery Study [COSS; NCT00029146], failed to show an overall benefit on 2-year stroke recurrence when extracranial-intracranial bypass surgery was added to standard medical therapy.